The Impact of Cold atmospheric plasma and PLGA/ Xylitol Nanoparticles on Dental Enamel (in vitro study ) - A. Ibrahim, Ghada; Eaman A. Al-Rubaee (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Plasma and nanotechnology are potentially effective preventive measures against dental caries. This study aims to determine the impact of cold atmospheric plasma and PLGA/Xylitol nanoparticles on dental enamel microhardness and morphological changes in dental enamel ultrastructure. Methodology: In this study, 56 maxillary first premolars were divided into five groups: one control group, four study groups, each with 11 teeth; 10 teeth were examined for microhardness; and one tooth was examined using SEM. A circular window was placed on the buccal surface of each tooth. Following a PH cycling technique to activate caries lesions on the tooth enamel, cold plasma was performed using predetermined parameters. The PLGA/Xylitol nanoparticle concentration was adjusted to 5%. The microhardness and morphological change were measured using micro vickers and Scanning Electron Microscopy (SEM) respectively, at three stages: sound, demineralization, and treatment. Result: Enamel microhardness values decreased highly significantly after the demineralization stage compared to the sound stage for all groups. After application of various agents, the microhardness values of all treated groups, excluding the control, increased highly significantly in comparison to the demineralization stage. The nanoparticles+ plasma group showed the highest microhardness recovery values. An SEM showed that the application of nanoparticles, nanoparticles + plasma, and plasma + nanoparticles caused the majority of surface defects to be repaired. Conclusion: The enamel surface treated with cold atmospheric plasma and PLGA/Xylitol nanoparticles yielded favourable results in terms of microhardness and SEM analysis, suggesting that this therapy could be recommended as a means of preventing dental caries.